Gestão e disputa pela água na sub-bacia do Riachão, Montes Claros/MG - Afonso, Priscilla Caires Santana (2007)
This research has as objective understand the process of management and argument for the water between farmers of the Riachão Valley. In this sense, the research was realized in communities of Lagoa do Barro, Lagoa da Tiririca and Pau D´Oleo, located in the high course of the sub-basin of Riachão in Montes Claros, Minas Gerais. The study it looked to analyse how the geraizeiros residents of these communities they had several of their strategies of survival compromised in virtue of the process of modernization agricultural Brazilian and principally proper to the peculiaritie of North os Minas Gerais. We can see, from a side, that the farmers keep on managing the water while a commom good according to their traditions and customs from another side, the businessmen farmer supported by the legislation define and defend the water as a good economical one, revealing divergences between local cultures and public politics. Conclude that in the rural space the priorization of the use of the water as a good economical one it limited it multiple use done by the local rural populations and it caused social exclusion and quarrel for the resource. It s necessary to know cultures and local logical to plan public politics or projects being developed, finding forms of the general one to meet the individual.